Religious scholars (Ulama') and political leaders (Umara') in the classical Malay texts: a comparative religion approach - Abdul Jalil, Mohd. Noh; Mohd Amin, Wan Mohd Azam (2016)
This paper aims in analyzing the roles of religious scholars (ulama’) and political leaders (umara’) during the Hindu-Buddhist and Islamic periods in the Malay Archipelago. Different roles have been entrusted to the religious authorities by the Malay rulers during the Hindu-Buddhist and Islamic periods. Analysis on the roles of both authorities is based on evidence found in two classical Malay texts namely the Sejarah Melayu (The Malay Annals) and Bustan al-Salatin (The Garden of Kings). This paper concludes how, after the spread of Islam to the Malay Archipelago relationship between religious scholars and secular leaders changed drastically. Religious scholars (‘ulama) maintained a less direct relationship with political leaders compared to the role of the Brahmin of the devaraja cult. They merely acted as moral advisors to the rulers who would decide whether to accept or to reject religious advice presented to them based on the needs at that time.